Use of electrostatic precipitation for excess ion trapping in an electrical aerosol detector - Panich Intra (2018)
In this paper, the technique of electrostatic precipitation was used to remove excess ions from a mixture with charged particles before collection on a filter in a Faraday cup electrometer of an electrical aerosol detector. The ion precipitator part of the detector was designed, constructed, and evaluated. An analytical model was developed to investigate ion and particle transports due to diffusion and space charge effects inside the ion precipitator. Experimental investigations were carried out for positive ions, the positively applied voltage at the wire electrode ranged from 10 to 150 V, ion flow rates ranged from 5 to 15 L/min, and the radial distance of the inlet was 0.15 and 14 mm at a fixed separation between the wire and outer electrodes. The calculation results showed that all charged particles of 10 nm in diameter could pass through the ion precipitator smoothly without precipitation at the outer electrode. For all ion flow rates, an increase in ion trap voltage produced an increase in ion collection efficiency of the precipitator. Experiments confirmed that the efficiency of the ion precipitator could increase to 99% at an ion trap voltage larger than 100 V for all ion flow rates. © 2011 Elsevier B.V.